2021
DOI: 10.7150/thno.49600
|View full text |Cite
|
Sign up to set email alerts
|

A novel STAT3 inhibitor W2014-S regresses human non-small cell lung cancer xenografts and sensitizes EGFR-TKI acquired resistance

Abstract: Constitutive activation of signal transducer and activator of transcription 3 (STAT3) is a common feature in human non-small cell lung cancer (NSCLC). STAT3 plays an important role in cancer progression as a driver oncogene and acquired resistance of targeted therapies as an alternatively activated pathway. W2014-S with pharmacophore structure of imidazopyridine, which was firstly reported to be utilized in STAT3 inhibitor discovery, was screened out as a potent STAT3 inhibitor from a library of small molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 25 publications
0
45
0
Order By: Relevance
“…STAT3 is also aberrantly hyperactivated in gastric cancer and promotes the genesis and development of gastric cancer [ 20 ]. Meanwhile, some studies showed that alternatively activated STAT3 plays a prominent role in mediating drug resistance to a broad spectrum of chemotherapies, such as cisplatin [ 21 ] and EGFR-TKIs [ 22 , 23 ]. As a transcription factor, STAT3 is also associated with oxidative response [ 24 ] and may be a potential regulator of ferroptosis.…”
Section: Introductionmentioning
confidence: 99%
“…STAT3 is also aberrantly hyperactivated in gastric cancer and promotes the genesis and development of gastric cancer [ 20 ]. Meanwhile, some studies showed that alternatively activated STAT3 plays a prominent role in mediating drug resistance to a broad spectrum of chemotherapies, such as cisplatin [ 21 ] and EGFR-TKIs [ 22 , 23 ]. As a transcription factor, STAT3 is also associated with oxidative response [ 24 ] and may be a potential regulator of ferroptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, treatment of tumor-bearing mice with the STAT3 inhibitor LL1 sensitizes resistant A549 NSCLC tumors to gefitinib and leads to a synergistic anti-tumor response [ 264 , 265 ]. These findings were corroborated in a separate study, where treatment of gefitinib- and erolotinib-resistant NSCLC with the STAT3 inhibitor W2014-S sensitized these cells to therapy in vitro and enhanced the anti-tumor efficacy of gefitinib in tyrosine kinase resistant lung cancer xenografts in vivo [ 238 ].…”
Section: Therapeutic Opportunitiesmentioning
confidence: 59%
“…Small molecule inhibitors that target the SH2 domain of STAT3 (e.g., C188-9, OPB-31121, OPB-51602, W2014-S, BBI-608) have demonstrated potent in vitro and in vivo anti-tumor activity in NSCLC models [ 70 , 236 , 237 , 238 ]. BBI-608 inhibits stemness gene expression, depletes CSCs, and overcomes cisplatin resistance in pre-clinical models of NSCLC [ 70 ], and showed encouraging signs of anti-cancer activity in a phase I/II study of NSCLC patients who received BBI-608 plus weekly paclitaxel (NCT01325441).…”
Section: Stat3 As a Therapeutic Targetmentioning
confidence: 99%
“…Previously, it was reported that tocilizumab could overcome IL-6-induced resistance to erlotinib, a 1st generation EGFR-TKI 13 . Also, we and others have reported that inhibition of STAT3 could reverse drug resistance to 1st generation EGFR-TKIs 10 , 14 . These data suggest that there is a difference of mechanism between 1st/2nd generation EGFR-TKI and osimertinib.…”
Section: Resultsmentioning
confidence: 81%